Laser heat shrink film and preparation method thereof
By adding modified chitin nanofibers, cellulose acetate propionate and modified montmorillonite to the POF heat shrink film, combined with laser holographic technology, the problems existing in the packaging laser application were solved, and laser heat shrink film with high transparency, high shrinkage and anti-counterfeiting functions were prepared.
Patent Information
- Application Number
- CN202411872333.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, POF heat shrink films have few problems in laser applications for packaging, and lack packaging films with high transparency, high shrinkage, anti-counterfeiting function and aesthetics.
A laser heat shrink film including a heat sealing layer, a heat shrinking layer and a laser layer is used. The heat sealing layer uses polypropylene and/or polyethylene, and the heat shrinking layer uses polypropylene and polyethylene, and modified chitin nanofibers, cellulose acetate propionate, modified montmorillonite and other materials are added thereto to improve the mechanical properties and anti-counterfeiting function of the film.
The combination of POF heat shrink film and laser holographic technology has been realized. The prepared laser heat shrink film has high transparency, high shrinkage, anti-counterfeiting function, durability, aesthetics and protection, and is suitable for packaging, fixing and protecting items.
Smart Images

Figure BDA0005196063930000101 
Figure BDA0005196063930000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of packaging films, and in particular to a laser heat shrink film and a preparation method thereof. Background Art
[0002] Heat shrink film is a packaging film that is stretched and oriented in a highly elastic state of the polymer during the production process, but shrinks when heated during use. It has the advantages of good flexibility, high transparency, and high shrinkage rate. The types of heat shrink film mainly include POF heat shrink film, PET heat shrink film, PVC heat shrink film, and PE heat shrink film.
[0003] Laser holographic technology has broad application prospects in the modern packaging industry, mainly due to its unique visual effects, anti-counterfeiting function and environmental protection characteristics. By giving heat shrink film better visual functions through laser holographic technology, it is expected to further meet more consumer needs and increase the added value of products.
[0004] The existing heat shrink film materials usually include polyester (PET), oriented polypropylene (BOPP), and polyvinyl chloride (PVC). PET film is used as the laser embossing carrier material. It has stable material and good printing suitability and is the most widely used laser film material on the market. BOPP film is used as the embossing carrier material. It is soft and suitable for lamination with cardboard. It is often used for packaging paper and paper bags. PVC film is used as the embossing carrier material. It has high transparency and can show the appearance and quality of the product.
[0005] POF heat shrink film is the abbreviation of biaxially oriented polyolefin shrink film. It is produced by a special process of advanced biaxially oriented three-layer and five-layer melt co-extrusion. It has the characteristics of high transparency, high shrinkage rate, high toughness, high heat sealing performance, antistatic, and excellent cold resistance. It is widely used in automotive products, plastic products, food, cosmetics and other fields. However, it has not yet been applied to laser POF heat shrink film for packaging. Summary of the invention
[0006] In order to improve the problem of limited application of POF heat shrinkable film and laser holographic technology, the present application provides a laser heat shrinkable film and a preparation method thereof.
[0007] The present application provides a laser heat shrink film, which adopts the following technical solution: A laser heat shrinkable film comprises a heat sealing layer, a heat shrinkable layer and a laser coating layer. The raw material of the heat sealing layer comprises polypropylene and / or polyethylene, the raw material of the heat shrinkable layer comprises polypropylene and polyethylene, and the laser coating layer is a holographic information layer or a laser ink layer.
[0008] By adopting the above technical solution, the raw materials of the heat-sealing layer include polypropylene and / or polyethylene. The heat-sealing layer is mainly used to seal the packaging material. The two layers of material are tightly combined by heating to ensure the integrity and sealing of the packaging. Polypropylene and polyethylene are both commonly used thermoplastics, which are easy to heat, mold and seal. The raw materials of the heat shrink layer include polypropylene and polyethylene. The heat shrink layer will shrink when heated, tightly fit the packaged items, and provide protection and fixation. The laser layer is a holographic information layer or a laser ink layer. The laser layer is mainly used to provide visual anti-counterfeiting, decoration or information display effects. The holographic information layer uses the interference and diffraction principles of light to record image information, while the laser ink layer achieves a unique visual effect through ink processing.
[0009] The laser heat shrink film includes a heat sealing layer, a heat shrink layer, and a laser coating layer, forming a sealed packaging system to prevent the intrusion of external factors such as air, moisture, and dust. Through the shrinkage effect, the packaged items are tightly wrapped to provide a stable fixing effect to prevent the items from shaking or shifting in the package. This application realizes the combination of POF heat shrink film and laser holographic technology. The prepared laser heat shrink film has high transparency, high shrinkage rate, anti-counterfeiting function, durability, aesthetics and protection.
[0010] Preferably, the raw materials of the heat shrinkable layer further include: modified chitin nanofibers, cellulose acetate propionate, modified montmorillonite, a leveling agent, a cross-linking agent, a slip agent, isopropyl alcohol, and an oxidant.
[0011] By adopting the above technical solution, the modified chitin nanofibers have the characteristics of ultra-high aspect ratio, excellent mechanical properties, high porosity, good transparency, etc., and can form a three-dimensional network structure in the heat shrink film, thereby significantly improving the tensile strength and toughness of the film, making the heat shrink film more reliable and not easy to break when packaging, fixing and protecting items. The modified chitin nanofibers also have natural antibacterial and barrier properties, which can effectively prevent the penetration of oxygen, water vapor and other harmful substances, and extend the shelf life of packaged items. Cellulose acetate propionate plays multiple roles in the heat shrink film, such as enhancing mechanical properties, improving heat shrinkage properties, improving barrier properties, adjusting transparency and gloss, and improving biocompatibility and degradability, so that the heat shrink film can withstand greater external forces and impacts.
[0012] The layered structure of modified montmorillonite can form nano-scale barriers in the film, blocking the penetration of foreign substances, thereby increasing the rigidity and strength of the film, improving the tensile strength and tear strength of the film, and reducing the deformation rate and yield point of the film, making the heat shrink film more reliable when packaging, fixing and protecting items. The leveling agent improves the fluidity and leveling of the coating, allowing the coating to form a flat, smooth and uniform coating during the drying and film-forming process. The cross-linking agent connects the polymer chains to each other to form a three-dimensional network structure, thereby enhancing the stability of the film, improving the chemical resistance and improving the mechanical properties, making the heat shrink film less likely to break or deform during use and having a longer service life.
[0013] The slip agent increases the lubricity of the film surface and reduces the friction coefficient, which helps to reduce the friction and wear of the film during packaging, transportation and use. It can also improve the smoothness and processability of the film, making it easier to handle and process the film during production. The use of isopropyl alcohol solvent allows the various compositions to be mixed and mixed to form a uniform coating material. The oxidant has the functions of preventing oxidative degradation, improving the durability of the film, improving processing performance, improving product quality, enhancing the transparency of the film and ensuring environmental safety.
[0014] Preferably, the method for preparing the modified chitin nanofibers comprises the following steps: (1) dispersing chitosan in an acetic acid aqueous solution to obtain a spinning solution, and electrospinning to obtain nanofibers; (2) dispersing the nanofibers in a sodium hydroxide solution, stirring for 1-2 hours, washing with water, and drying to obtain treated nanofibers; (3) dispersing the treated nanofibers in an aqueous epoxy resin solution, adding modified carbon nanotubes and nano-silicon dioxide, stirring at a temperature of 70-75° C. for 1-2 hours, and drying at 85-90° C. to obtain modified chitin nanofibers.
[0015] By adopting the above technical scheme, chitosan is dissolved in an acetic acid aqueous solution to form a uniform spinning solution, and the obtained nanofibers have excellent biocompatibility, safety, degradability, and broad-spectrum antibacterial properties. In addition, they also have good mechanical properties and chemical stability. The nanofibers are treated with sodium hydroxide solution to remove impurities and residues on the surface of the nanofibers, making the surface of the nanofibers rougher, increasing their specific surface area, changing the surface properties of the nanofibers, and enhancing the stability and dispersibility of the nanofibers.
[0016] The aqueous epoxy resin solution has good adhesion and mechanical properties, the modified carbon nanotubes have good dispersibility and compatibility with the matrix, and the nano-silicon dioxide has excellent reinforcement effect and thermal stability, which can improve the hardness and wear resistance of the material. The aqueous epoxy resin solution allows the modified carbon nanotubes and nano-silicon dioxide to adhere to the surface of the nanofibers, improving the mechanical properties of the nanofibers, including tensile strength, bending strength and toughness. The obtained modified chitin nanofibers are used in heat shrinkable films, which significantly improve the mechanical strength, heat resistance, barrier properties, and dispersibility of the film, and can withstand greater external forces and pressures when packaging, fixing and protecting items, and are not easy to deform or break.
[0017] Preferably, the mass ratio of the chitosan, the modified carbon nanotubes and the nano-silicon dioxide is 1g:80-90mg:0.2-0.3g.
[0018] By adopting the above technical solution, the mass ratio of chitosan, modified carbon nanotubes and nano-silicon dioxide is further limited within a certain range, and the obtained modified chitosan nanofibers have good mechanical strength and thermal stability. Chitosan has excellent mechanical properties and toughness, and the modified carbon nanotubes can form a network structure, effectively disperse stress, and improve the tear strength and wear resistance of chitosan. Nano-silicon dioxide plays a filling and reinforcing role, making chitosan harder and more wear-resistant. There is a synergistic effect between chitosan, modified carbon nanotubes and nano-silicon dioxide, which further improves the comprehensive performance of the film, such as improving the tensile strength, elongation at break, impact toughness, thermal stability and barrier properties of chitosan. It will be subsequently applied to laser heat shrink film to improve the corresponding performance of the film and make the film easier to operate and fit during the packaging process.
[0019] Preferably, the method for preparing the modified carbon nanotubes comprises the following steps: (1) dispersing carbon nanotubes in concentrated sulfuric acid solution, ultrasonicating for 20-25 min, stirring at a temperature of 180-190° C., refluxing for 6-8 h, filtering, washing until neutral, and drying to obtain acidified carbon nanotubes; (2) The acidified carbon nanotubes are dispersed in an ethanol aqueous solution, vinyl triethoxysilane and chitosan are added, the mixture is stirred at a temperature of 55-60° C. for 1-2 hours, and freeze-dried to obtain the modified carbon nanotubes.
[0020] By adopting the above technical scheme, the carbon nanotubes are dispersed in a concentrated sulfuric acid solution, ultrasonic treatment is performed to break up the agglomerates to ensure the uniform dispersion of the carbon nanotubes in the solution, stirring and reflux for a period of time at high temperature to promote the acidification reaction and ensure the full contact between the carbon nanotubes and the concentrated sulfuric acid, so that the surface of the acidified carbon nanotubes has increased functional groups such as hydroxyl and carbonyl, thereby improving the hydrophilicity and reaction activity of the carbon nanotubes.
[0021] Disperse the acidified carbon nanotubes in an ethanol-water solution to ensure uniform distribution of the carbon nanotubes in the solution, add vinyl triethoxysilane and chitosan, which react with the functional groups on the surface of the carbon nanotubes to form chemical bonds. At the same time, chitosan will also undergo a self-crosslinking reaction to form a network structure, which enhances the reactivity, biocompatibility, stability and mechanical properties of the carbon nanotubes. In combination with chitin and nano-silica, the mechanical strength and thermal stability of the modified chitin nanofibers are improved, and the mechanical properties of the heat shrink film are subsequently improved to prevent the film from breaking or deforming when subjected to external forces, increase the tear strength and wear resistance of the film, and make the film more durable.
[0022] Preferably, the preparation method of the modified montmorillonite comprises the following steps: (1) dispersing montmorillonite in deionized water, ultrasonicating, adding sodium hexametasulfate, settling, decanting the upper suspension, centrifuging, washing, and drying to obtain purified montmorillonite; (2) dispersing the purified montmorillonite in deionized water, adding the modified carbon fiber and sodium stearate, stirring at a temperature of 60-65° C. for 1-2 h, and drying to obtain a mixture; (3) Spraying a sodium carboxymethyl cellulose aqueous solution onto the surface of the mixture while stirring, and drying to obtain modified montmorillonite.
[0023] By adopting the above technical solution, sodium hexametaphosphate is used as a dispersant to form a soluble complex with the metal ions between the montmorillonite layers, thereby facilitating the dispersion and purification of montmorillonite. After the addition of sodium hexametaphosphate, the montmorillonite particles gradually settle to the bottom of the solution under the action of gravity, and the upper suspension is decanted. This part of the suspension mainly contains unsettled montmorillonite particles and a small amount of dispersant, which is centrifuged and washed to obtain purified montmorillonite.
[0024] Purified montmorillonite is dispersed in deionized water, and modified carbon fiber and sodium stearate are added. The modified carbon fiber has better dispersibility and compatibility with other materials. Sodium stearate improves the dispersibility of montmorillonite and carbon fiber in the solution and promotes the interaction between them. In the obtained mixture, a certain interaction and combination are formed between montmorillonite, modified carbon fiber and sodium stearate, which gives the mixture some special properties, such as higher strength, better heat resistance and chemical corrosion resistance.
[0025] Sodium carboxymethyl cellulose has good film-forming, adhesion and water retention properties. It is evenly sprayed on the surface of a mixture of purified montmorillonite, modified carbon fiber and sodium stearate, making the modified carbon fiber and sodium stearate more stably adhere to the surface of montmorillonite, improving the dispersibility, stability and mechanical properties of the modified montmorillonite. It is subsequently applied to heat shrinkable films to significantly improve the mechanical properties of the heat shrinkable films. When the modified montmorillonite is evenly dispersed in the heat shrinkable film, it acts as a reinforcing agent to increase the tensile strength, bending strength and modulus of the film, making the heat shrinkable film more durable and less prone to rupture or deformation when subjected to external forces.
[0026] Preferably, the mass ratio of the montmorillonite, the modified carbon fiber and the sodium carboxymethyl cellulose aqueous solution is 1:0.3-0.4:0.07-0.09.
[0027] By adopting the above technical scheme, the mass ratio of montmorillonite, modified carbon fiber and sodium carboxymethyl cellulose aqueous solution is further limited within a certain range, and the obtained modified montmorillonite has good mechanical properties and thermal stability. The modified carbon fiber can be loaded on the surface and pores of montmorillonite to enhance the mechanical strength and toughness of montmorillonite. The sodium carboxymethyl cellulose aqueous solution has a certain viscosity and film-forming property, so that the montmorillonite and the modified carbon fiber are closely bonded, and the overall performance of the montmorillonite is jointly improved. The synergistic effect of montmorillonite, modified carbon fiber and sodium carboxymethyl cellulose aqueous solution subsequently improves the comprehensive performance of the heat shrink film, including mechanical properties, thermal stability, barrier properties, electrical conductivity and thermal conductivity.
[0028] Preferably, the preparation method of the modified carbon fiber comprises the following steps: grinding carbon fiber with a length of 50-100 microns until the length drops to less than 0.5 microns and the aspect ratio is less than 10 to obtain pretreated carbon fiber, dispersing the pretreated carbon fiber in deionized water, adding sodium dodecylbenzene sulfonate, water glass and nano nickel, stirring at a temperature of 70-75°C for 2-3h, and drying to obtain modified carbon fiber.
[0029] By adopting the above technical solution, sodium dodecylbenzene sulfonate can improve the compatibility between carbon fiber and deionized water, improve the dispersion effect, reduce the surface tension of carbon fiber, and make it easier to disperse evenly in deionized water. Water glass is used as an adhesive or reinforcing agent to improve the binding force between carbon fiber and nano-nickel, so that nano-nickel can stably adhere to the surface of carbon fiber, improve the strength, modulus, corrosion resistance and heat resistance of carbon fiber, and the obtained modified carbon fiber has better comprehensive performance, improves the corresponding performance of montmorillonite, and is subsequently applied to heat shrink film to improve the tensile strength, tear strength and wear resistance of heat shrink film, so that the heat shrink film is more durable when subjected to external force, and is not easy to break or deform, thereby improving the safety and stability of packaged items.
[0030] Preferably, the antioxidant is a compound of antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1-2:1.
[0031] By adopting the above technical solution, the compound of antioxidant 1010 and antioxidant 168 produces a synergistic effect, which can provide more comprehensive and stronger antioxidant protection, improve the weather resistance and durability of the heat shrinkable film, and extend the service life.
[0032] In a second aspect, the present application also provides a method for preparing a laser heat shrink film, comprising the following steps: (1) melt-extrude and blow-mold polypropylene and / or polyethylene to obtain a heat-sealing layer; (2) mixing polypropylene and polyethylene uniformly, and obtaining a heat shrinkable layer through a multi-layer co-extrusion and secondary blow molding process; (3) The heat sealing layer and the heat shrinking layer are bonded by an adhesive, and the holographic information layer or the laser ink layer is transferred to the heat shrinking layer to obtain a laser heat shrinking film.
[0033] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing laser heat shrinkable film. The obtained laser heat shrinkable film has good mechanical properties and mechanical strength.
[0034] Preferably, when the raw materials of the heat shrinkable layer further include: modified chitin nanofibers, cellulose acetate propionate, modified montmorillonite, a leveling agent, a cross-linking agent, a slip agent, isopropyl alcohol, and an oxidant, in the method for preparing a laser heat shrinkable film, in step (2), polypropylene, polyethylene, modified chitin nanofibers, cellulose acetate propionate, modified montmorillonite, a leveling agent, a cross-linking agent, a slip agent, isopropyl alcohol, and an oxidant are uniformly mixed, and the heat shrinkable layer is obtained through a multi-layer co-extrusion and secondary blow molding process.
[0035] By adopting the above technical solution, the obtained heat shrinkable layer has good mechanical strength, wear resistance and stability.
[0036] In summary, this application has the following beneficial effects: 1. The laser heat shrink film in the present application includes a heat sealing layer, a heat shrinking layer, and a laser coating layer to form a sealed packaging system to prevent the intrusion of external factors such as air, moisture, and dust. Through the shrinkage effect, the packaged items are tightly wrapped to provide a stable fixing effect to prevent the items from shaking or shifting in the package, thereby realizing the combination of POF heat shrink film and laser holographic technology. The prepared laser heat shrink film has high transparency, high shrinkage rate, anti-counterfeiting function, durability, aesthetics and protection.
[0037] 2. The modified chitin nanofibers in this application have the characteristics of ultra-high aspect ratio, excellent mechanical properties, high porosity, good transparency, etc., and can form a three-dimensional network structure in the heat shrinkable film, thereby significantly improving the tensile strength and toughness of the film, making the heat shrinkable film more reliable and less prone to damage when packaging, fixing and protecting items.
[0038] 3. The layered structure of the modified montmorillonite in this application can form nano-scale barriers in the film to block the penetration of foreign substances, thereby increasing the stiffness and strength of the film, improving the tensile strength and tear strength of the film, reducing the deformation rate and yield point of the film, and making the heat shrink film more reliable when packaging, fixing and protecting items. DETAILED DESCRIPTION
[0039] The present application is further described in detail below with reference to the embodiments.
[0040] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0041] Preparation example of modified chitin nanofibers Preparation Example 1-1 The preparation method of modified chitin nanofibers comprises the following steps: (1) 1.5 kg of chitosan was dispersed in 2 L of 8% acetic acid aqueous solution to obtain a spinning solution, and electrospinning was performed to obtain nanofibers with a diameter of 300 nm and a length of 20 mm; wherein the spinning was performed at a propulsion speed of 0.04 mL / min, and the positive and negative voltages were set to 20 kV and -1 kV, respectively; (2) dispersing the nanofibers in 2.2 L of a 10% sodium hydroxide solution, stirring for 1.5 h, washing with water, and drying to obtain treated nanofibers; (3) The treated nanofibers were dispersed in an aqueous epoxy resin solution, modified carbon nanotubes and nano-silica were added, stirred at 75°C for 1.5 h, and dried at 90°C to obtain modified chitin nanofibers; the aqueous epoxy resin was purchased from Shandong Changyao New Materials Co., Ltd., and 0.3 kg of aqueous epoxy resin was dispersed in 4 L of deionized water to obtain an aqueous epoxy resin solution.
[0042] The mass ratio of chitosan, modified carbon nanotubes and nano-silicon dioxide is 1g:80mg:0.3g.
[0043] The method for preparing modified carbon nanotubes comprises the following steps: (1) 20 g of carbon nanotubes were dispersed in 5 L of 98% concentrated sulfuric acid solution, ultrasonicated for 25 min, stirred at 180° C. for 20 min, refluxed for 8 h, filtered, washed until neutral, and dried to obtain acidified carbon nanotubes; (2) The acidified carbon nanotubes were dispersed in 4 L of 70% ethanol aqueous solution, vinyl triethoxysilane and chitosan were added, stirred at 60°C for 2 h, and freeze-dried to obtain modified carbon nanotubes, and the required amount was used in the preparation method of modified chitin nanofibers.
[0044] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (3), no modified carbon nanotubes are added.
[0045] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no nano-silicon dioxide is added.
[0046] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of chitosan, modified carbon nanotubes and nano-silicon dioxide is 1g:90mg:0.2g.
[0047] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of chitosan, modified carbon nanotubes and nano-silicon dioxide is 1g:70mg:0.8g.
[0048] Preparation Example 1-6 The difference from Preparation Example 1-1 is that vinyltriethoxysilane is not added in the preparation method of the modified carbon nanotubes.
[0049] Preparation Example 1-7 The difference from Preparation Example 1-1 is that chitosan is not added in the preparation method of modified carbon nanotubes.
[0050] Preparation example of modified montmorillonite Preparation Example 2-1 The preparation method of modified montmorillonite comprises the following steps: (1) 1.5 kg of montmorillonite was dispersed in 2 L of deionized water, ultrasonicated for 1 h, 0.3 kg of sodium hexametasulfate was added, the mixture was allowed to settle, the upper suspension was decanted, centrifuged, washed, and dried to obtain purified montmorillonite; (2) dispersing the purified montmorillonite in 1.5 L of deionized water, adding the modified carbon fiber and 0.2 kg of sodium stearate, stirring at 65 ° C for 2 h, and drying to obtain a mixture; (3) Spraying a sodium carboxymethyl cellulose aqueous solution onto the surface of the mixture while stirring, and drying to obtain modified montmorillonite.
[0051] The mass ratio of montmorillonite, modified carbon fiber and sodium carboxymethyl cellulose aqueous solution is 1:0.3:0.09.
[0052] The preparation method of modified carbon fiber comprises the following steps: grinding 1 kg of carbon fiber with a length of 50-100 microns to a length below 0.5 microns and an aspect ratio of less than 10 to obtain pretreated carbon fiber, dispersing the pretreated carbon fiber in 2L of deionized water, adding 0.2 kg of sodium dodecylbenzene sulfonate, 0.3 kg of water glass and 0.5 kg of nano nickel, stirring at a temperature of 75°C for 3 hours, drying to obtain modified carbon fiber, and taking the required amount for use in the preparation method of modified montmorillonite.
[0053] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no modified carbon fiber is added.
[0054] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (2), no sodium carboxymethyl cellulose aqueous solution is added.
[0055] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of montmorillonite, modified carbon fiber and sodium carboxymethyl cellulose aqueous solution is 1:0.4:0.07.
[0056] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of montmorillonite, modified carbon fiber and sodium carboxymethyl cellulose aqueous solution is 1:0.1:0.14.
[0057] Preparation Example 2-6 The difference from Preparation Example 2-1 is that water glass is not added in the preparation method of the modified carbon fiber.
[0058] Preparation Example 2-7 The difference from Preparation Example 2-1 is that nano-nickel is not added in the preparation method of the modified carbon fiber. Example
[0059] Example 1 A laser heat shrinkable film comprises a heat sealing layer, a heat shrinkable layer and a laser coating layer, wherein the raw material of the heat sealing layer comprises polypropylene, the raw material of the heat shrinkable layer comprises polypropylene and polyethylene, and the laser coating layer is a holographic information layer; The method for preparing the laser heat shrinkable film comprises the following steps: (1) The raw materials of the heat sealing layer are melt-extruded and blow-molded to obtain a heat sealing layer with a thickness of 8 μm; wherein the raw materials are melt-blended at a temperature of 130° C., extruded by a twin-screw extruder at a screw speed of 45 r / min, a temperature of 120° C. in the first zone, 160° C. in the second zone, 170° C. in the third zone, and a die head temperature of 160° C., and blow-molded by a blown film unit at a temperature of 180° C.
[0060] (2) Polypropylene and polyethylene are uniformly mixed, and a heat shrink layer with a thickness of 18 μm is obtained through a three-layer co-extrusion and secondary blow molding process; the body temperature of the first extruder is set to 180°C, and the neck temperature of the extruder is 200°C; the body temperature of the second extruder is set to 210°C, the body temperature of the extruder is set to 230°C, and the neck temperature of the extruder is 240°C; the body temperature of the third extruder is set to 220°C, the body temperature of the extruder is set to 210°C, and the neck temperature of the third extruder is 220°C; the first extruder, the second extruder, and the third extruder are all equipped with independent circulating cooling systems; the temperature of the three-layer co-extrusion head of the three-layer co-extrusion system is 235°C; and blow molding is performed at a temperature of 190°C by a blow molding film unit.
[0061] (3) The heat sealing layer and the heat shrinking layer are bonded by an adhesive, and the laser coating layer is transferred to the heat shrinking layer to obtain a laser heat shrinking film; the adhesive is a polyurethane adhesive, and the layer thickness of the adhesive is 2 μm.
[0062] The holographic information substrate is transferred to the heat shrinkable layer by embossing, so that the surface of the film material obtains a laser effect to obtain a laser heat shrinkable film, and the embossing temperature is 75°C.
[0063] Example 2 A laser heat shrinkable film, which differs from Example 1 in that the raw material of the heat sealing layer includes polyethylene, the laser layer is a laser ink layer, and the laser ink is evenly coated on the heat shrinkable layer by printing, and dried at 110°C, so that the heat shrinkable film material achieves a laser visual effect, thereby obtaining a laser heat shrinkable film; the laser ink is purchased from Dongguan Mingbo Anti-counterfeiting Technology Co., Ltd., and the coating thickness is 5 μm.
[0064] Example 3 A laser heat shrinkable film, which differs from Example 1 in that the raw materials of the heat shrinkable layer also include: 10kg modified chitin nanofiber, 4kg cellulose acetate propionate, 8kg modified montmorillonite, 0.1kg leveling agent, 0.2kg cross-linking agent, 0.5kg slip agent, 50kg isopropyl alcohol, and 0.3kg oxidant.
[0065] The leveling agent is polydimethylsiloxane, the cross-linking agent is diethylenetriamine, the slip agent is stearic acid amide, and the antioxidant is a compound of antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1.5:1.
[0066] The preparation method of the laser heat shrink film comprises the following steps: in step (2), polypropylene, polyethylene, modified chitin nanofibers, cellulose acetate propionate, modified montmorillonite, a leveling agent, a crosslinking agent, a slip agent, isopropyl alcohol, and an oxidant are uniformly mixed, and a heat shrinkable layer is obtained through a three-layer co-extrusion and secondary blow molding process.
[0067] The modified chitosan nanofiber was prepared by using Preparation Example 1-1, and the modified montmorillonite was prepared by using Preparation Example 2-1.
[0068] Example 4 A laser heat shrinkable film, which is different from Example 3 in that the modified chitin nanofiber is prepared using Preparation Example 1-2.
[0069] Example 5 A laser heat shrinkable film, which is different from Example 3 in that the modified chitin nanofibers are prepared using Preparation Examples 1-3.
[0070] Example 6 A laser heat shrinkable film, which is different from Example 3 in that the modified chitin nanofibers are prepared using Preparation Examples 1-4.
[0071] Example 7 A laser heat shrinkable film, which is different from Example 3 in that the modified chitin nanofibers are prepared using Preparation Examples 1-5.
[0072] Example 8 A laser heat shrinkable film, which is different from Example 3 in that the modified chitin nanofibers are prepared using Preparation Examples 1-6.
[0073] Example 9 A laser heat shrinkable film, which is different from Example 3 in that the modified chitin nanofibers are prepared using Preparation Examples 1-7.
[0074] Example 10 A laser heat shrinkable film, which is different from Example 3 in that the modified montmorillonite is prepared using Preparation Example 2-2.
[0075] Embodiment 11 A laser heat shrinkable film, which is different from Example 3 in that the modified montmorillonite is prepared using Preparation Example 2-3.
[0076] Example 12 A laser heat shrinkable film, which is different from Example 3 in that the modified montmorillonite is prepared using Preparation Examples 2-4.
[0077] Embodiment 13 A laser heat shrinkable film, which is different from Example 3 in that the modified montmorillonite is prepared using Preparation Examples 2-5.
[0078] Embodiment 14 A laser heat shrinkable film, which is different from Example 3 in that the modified montmorillonite is prepared using Preparation Examples 2-6.
[0079] Embodiment 15 A laser heat shrinkable film, which is different from Example 3 in that the modified montmorillonite is prepared using Preparation Examples 2-7.
[0080] Comparative Example Comparative Example 1 A laser heat shrinkable film, which is different from Example 3 in that modified chitin nanofibers are not added.
[0081] Comparative Example 2 A laser heat shrinkable film, which is different from Example 3 in that the modified chitosan nanofibers are replaced by an equal amount of chitosan nanofibers.
[0082] Comparative Example 3 A laser heat shrinkable film, which is different from Example 3 in that modified montmorillonite is not added.
[0083] Comparative Example 4 A laser heat shrinkable film, which is different from Example 3 in that the modified montmorillonite is replaced by an equal amount of montmorillonite.
[0084] Performance testing The laser heat shrinkable films prepared in Examples 1-15 and Comparative Examples 1-4 were subjected to performance tests. The mechanical properties were measured according to the standard GB / T 13519-2016 "Polyethylene heat shrinkable film for packaging" to determine the tensile strength, nominal strain at break, and right-angle tear strength of the samples; the shrinkage rate was tested according to the GB / T 13519-1992 standard, and the test results are shown in Table 1.
[0085] Table 1 Test data of embodiments and comparative examples As can be seen from Table 1, the heat shrinkable films prepared in Examples 1-2 of the present application have good mechanical properties, heat shrinkage and mechanical strength, wherein the longitudinal tensile strength of Example 1 reaches 22.3MPa, the transverse tensile strength reaches 16.5MPa, the longitudinal nominal strain at break is 493%, the transverse nominal strain at break is 380%, the right-angle tear strength is 94kN / m, the longitudinal heat shrinkage rate is 59%, and the transverse heat shrinkage rate is 19%. This indicates that the prepared laser heat shrinkable film has good mechanical properties and mechanical strength, and the various components cooperate with each other to improve the tensile strength, tear strength and heat shrinkage of the heat shrinkable film, and extend the service life of the heat shrinkable film.
[0086] The raw materials of the heat shrinkable layer of Example 3 also include other added components. As can be seen from Table 1, the longitudinal tensile strength reaches 38.8MPa, the transverse tensile strength reaches 32.7MPa, the longitudinal nominal strain at break is 536%, the transverse nominal strain at break is 429%, the right-angle tear strength is 116kN / m, the longitudinal heat shrinkage rate is 78%, and the transverse heat shrinkage rate is 37%. This shows that the modified chitin nanofiber added in this application can form a three-dimensional network structure in the heat shrinkable film, improve the tensile strength and toughness of the film; the layered structure of the modified montmorillonite can form nano-scale obstacles in the film, improving the tensile strength and tear strength of the film.
[0087] In the preparation methods of modified chitin nanofibers in Examples 4-5, modified carbon nanotubes and nano-silica are not added respectively. In Examples 6-7, the mass ratio of chitin, modified carbon nanotubes and nano-silica is changed. It can be seen from Table 1 that the test results of longitudinal / transverse tensile strength, longitudinal / transverse nominal strain at break, right-angle tear strength, and longitudinal / transverse heat shrinkage of Examples 4-5 are significantly worse than those of Examples 3 and 6, while the corresponding performance test of Example 7 is better than that of Examples 4-5, but worse than that of Examples 3 and 6, indicating that there is a synergistic effect between chitin, modified carbon nanotubes and nano-silica, which improves the comprehensive properties of the film such as tensile strength, elongation at break, impact toughness, and thermal stability, and is subsequently applied to laser heat shrinkable film to improve the corresponding properties of the film.
[0088] In the preparation method of modified carbon nanotubes in Examples 8-9, vinyl triethoxysilane and chitosan are not added respectively. As can be seen from Table 1, the test results of longitudinal / transverse tensile strength, longitudinal / transverse nominal strain at break, right-angle tear strength, and longitudinal / transverse thermal shrinkage rate of Examples 8-9 are significantly worse than those of Example 3, but better than those of Example 4, indicating that vinyl triethoxysilane and chitosan will react with the functional groups on the surface of carbon nanotubes to form chemical bonds, thereby improving the mechanical strength and thermal stability of the modified chitin nanofibers, preventing the membrane from breaking or deforming when subjected to external forces, increasing the tear strength and wear resistance of the membrane, and making the membrane more durable.
[0089] In the preparation method of modified montmorillonite in Examples 10-11, modified carbon fiber and sodium carboxymethyl cellulose aqueous solution are not added respectively. In Examples 12-13, the mass ratio of montmorillonite, modified carbon fiber and sodium carboxymethyl cellulose aqueous solution is changed. It can be seen from Table 1 that the test results of longitudinal / transverse tensile strength, longitudinal / transverse nominal strain at break, right-angle tear strength, and longitudinal / transverse thermal shrinkage of Examples 10-11 are significantly worse than those of Examples 3 and 12, while the corresponding performance test of Example 13 is better than that of Examples 10-11, but worse than that of Examples 3 and 12, indicating that the modified carbon fiber can be loaded on the surface and pores of montmorillonite to enhance the mechanical strength and toughness of montmorillonite, and the sodium carboxymethyl cellulose aqueous solution has certain viscosity and film-forming properties, so that the montmorillonite and the modified carbon fiber are closely bonded, thereby jointly improving the overall performance of the montmorillonite.
[0090] In the preparation method of the modified carbon fiber of Examples 14-15, water glass and nano-nickel are not added respectively. As can be seen from Table 1, the test results of the longitudinal / transverse tensile strength, longitudinal / transverse nominal strain at break, right-angle tear strength, and longitudinal / transverse thermal shrinkage of Examples 14-15 are significantly worse than those of Example 3, but better than those of Example 10, indicating that water glass, as an adhesive or reinforcing agent, improves the bonding force between carbon fiber and nano-nickel, so that nano-nickel can stably adhere to the surface of carbon fiber, thereby improving the strength, modulus, corrosion resistance and heat resistance of carbon fiber, and the obtained modified carbon fiber has better comprehensive performance.
[0091] In Comparative Example 1 and Comparative Example 3, no modified chitin nanofibers and modified montmorillonite are added, respectively. As can be seen from Table 1, the test results of the longitudinal / transverse tensile strength, longitudinal / transverse nominal strain at break, right-angle tear strength, and longitudinal / transverse thermal shrinkage of Comparative Example 1 and Comparative Example 3 are significantly worse than those of Example 3. However, due to Examples 1-2, it is shown that the modified chitin nanofibers and montmorillonite of the present application have good mechanical strength and thermal shrinkage, making the heat shrinkable film more reliable and not easy to break when packaging, fixing and protecting articles.
[0092] In Comparative Examples 2 and 4, the modified chitin nanofibers are replaced by an equal amount of chitin nanofibers, and the modified montmorillonite is replaced by an equal amount of montmorillonite. It can be seen from Table 1 that the test results of the longitudinal / transverse tensile strength, longitudinal / transverse nominal strain at break, right-angle tear strength, and longitudinal / transverse thermal shrinkage rate of Comparative Examples 2 and 4 are significantly worse than those of Example 3, but better than those of Comparative Examples 1 and 3, indicating that the modified chitin nanofibers and modified montmorillonite in the present application have good mechanical properties, thereby improving the mechanical properties of the heat shrinkable film and maintaining the structural strength and stability of the heat shrinkable film.
[0093] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A laser heat shrink film, characterized in that: It comprises a heat sealing layer, a heat shrinking layer and a laser coating layer. The raw material of the heat sealing layer comprises polypropylene and / or polyethylene. The raw material of the heat shrinking layer comprises polypropylene and polyethylene. The laser coating layer is a holographic information layer or a laser ink layer.
2. The laser heat shrink film according to claim 1, characterized in that: The raw materials of the heat shrinkable layer also include: modified chitin nanofiber, cellulose acetate propionate, modified montmorillonite, a leveling agent, a crosslinking agent, a slip agent, isopropyl alcohol, and an oxidant.
3. The laser heat shrink film according to claim 2, characterized in that: The method for preparing the modified chitin nanofiber comprises the following steps: (1) dispersing chitosan in an acetic acid aqueous solution to obtain a spinning solution, and electrospinning to obtain nanofibers; (2) dispersing the nanofibers in a sodium hydroxide solution, stirring for 1-2 hours, washing with water, and drying to obtain treated nanofibers; (3) Dispersing the treated nanofibers in an aqueous epoxy resin solution, adding modified carbon nanotubes and nano-silica, stirring at a temperature of 70-75°C for 1-2 hours, and drying at 85-90°C to obtain modified chitin nanofibers.
4. The laser heat shrink film according to claim 3, characterized in that: The mass ratio of the chitin, the modified carbon nanotube and the nano silicon dioxide is 1g:80-90mg:0.2-0.3g.
5. The laser heat shrink film according to claim 3, characterized in that: The method for preparing the modified carbon nanotubes comprises the following steps: (1) dispersing carbon nanotubes in concentrated sulfuric acid solution, ultrasonicating for 20-25 min, stirring at 180-190°C, refluxing for 6-8 h, filtering, washing to neutrality, and drying to obtain acidified carbon nanotubes; (2) The acidified carbon nanotubes are dispersed in an ethanol aqueous solution, vinyl triethoxysilane and chitosan are added, the mixture is stirred at a temperature of 55-60° C. for 1-2 hours, and freeze-dried to obtain the modified carbon nanotubes.
6. The laser heat shrink film according to claim 2, characterized in that: The preparation method of the modified montmorillonite comprises the following steps: (1) dispersing montmorillonite in deionized water, ultrasonicating, adding sodium hexametasulfate, settling, decanting the upper suspension, centrifuging, washing, and drying to obtain purified montmorillonite; (2) dispersing the purified montmorillonite in deionized water, adding the modified carbon fiber and sodium stearate, stirring at a temperature of 60-65° C. for 1-2 hours, and drying to obtain a mixture; (3) Spraying a sodium carboxymethyl cellulose aqueous solution onto the surface of the mixture while stirring, and drying to obtain modified montmorillonite.
7. The laser heat shrink film according to claim 6, characterized in that: The mass ratio of the montmorillonite, the modified carbon fiber and the sodium carboxymethyl cellulose aqueous solution is 1:0.3-0.4:0.07-0.
09.
8. The laser heat shrink film according to claim 6, characterized in that: The preparation method of the modified carbon fiber comprises the following steps: grinding carbon fiber with a length of 50-100 microns until the length drops to less than 0.5 microns and the aspect ratio is less than 10 to obtain pretreated carbon fiber; dispersing the pretreated carbon fiber in deionized water; adding sodium dodecylbenzene sulfonate, water glass and nano nickel; stirring at a temperature of 70-75°C for 2-3 hours; and drying to obtain the modified carbon fiber.
9. The laser heat shrink film according to claim 1, characterized in that: The antioxidant is a compound of antioxidant 1010 and antioxidant 168, and the mass ratio of antioxidant 1010 to antioxidant 168 is 1-2:
1.
10. The method for preparing a laser heat shrinkable film according to claim 1, characterized in that: The steps include: (1) Melting, extruding and blow-molding polypropylene and / or polyethylene to obtain a heat-sealing layer; (2) mixing polypropylene and polyethylene uniformly, and obtaining a heat shrinkable layer through a multi-layer co-extrusion and secondary blow molding process; (3) The heat sealing layer and the heat shrinking layer are bonded by an adhesive, and the holographic information layer or the laser ink layer is transferred to the heat shrinking layer to obtain a laser heat shrinking film.
Citation Information
Patent Citations
High-transparency polyethylene heat shrink film and preparation method thereof
CN116728930A
Power battery heat dissipation material and preparation method thereof
CN118027638A
Multi-layer composite thermoregulation cotton and preparation method thereof
CN118756502A
Efficient heat dissipation graphite material for LED large-screen display and preparation method of efficient heat dissipation graphite material
CN119110558A
Laser holographic antifake shrinkage membrane
CN2630151Y